2023
DOI: 10.3389/fncel.2023.1106547
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid masquerade: Microglial transcriptional signatures in retinal development and disease

Abstract: Microglia are dynamic guardians of neural tissue and the resident immune cells of the central nervous system (CNS). The disease-associated microglial signature (DAM), also known as the microglial neurodegenerative phenotype (MGnD), has gained significant attention in recent years as a fundamental microglial response common to various neurodegenerative disease pathologies. Interestingly, this signature shares many features in common with developmental microglia, suggesting the existence of recycled gene program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 177 publications
(315 reference statements)
0
2
0
Order By: Relevance
“…We previously found that murine retinal microglia gene expression is heterogeneous and dynamic throughout development (5, 6). Notably, we showed that a majority of microglia early in postnatal retina express CD11c (Integrin αX, complement receptor 4, Itgax ) and were remarkably similar to CD11c-expressing (CD11c+) microglia of the developing and diseased brain (6, 7). By single-cell RNA sequencing, we found heterogeneity in CD11c+ microglia, but all CD11c+ microglia expressed genes associated with phagocytosis and lysosomal function (6).…”
Section: Introductionmentioning
confidence: 91%
“…We previously found that murine retinal microglia gene expression is heterogeneous and dynamic throughout development (5, 6). Notably, we showed that a majority of microglia early in postnatal retina express CD11c (Integrin αX, complement receptor 4, Itgax ) and were remarkably similar to CD11c-expressing (CD11c+) microglia of the developing and diseased brain (6, 7). By single-cell RNA sequencing, we found heterogeneity in CD11c+ microglia, but all CD11c+ microglia expressed genes associated with phagocytosis and lysosomal function (6).…”
Section: Introductionmentioning
confidence: 91%
“…The mechanisms and consequences of inflammation in glaucoma are well documented and will not be a focus of this review. For more detailed information about the influence of microglial ( 72 75 ), astrocyte ( 76 ), Müller cells ( 77 ), complement ( 78 , 79 ) and oxidative stress ( 78 ), immune signalling or inflammation in general ( 80 , 81 ) on glaucoma pathology, we direct the reader to other reviews. While inflammatory signalling mechanisms are well understood, we know very little about what metabolic changes occur because of, or even preceding, these inflammatory reactions.…”
Section: Glial Metabolic Changes In Glaucomamentioning
confidence: 99%